Analisis Formulasi Kebijakan Surat Keputusan Walikota Padang Nomor 378 Tahun 2022 Tentang Tim Pengawasan Bangunan Gedung dan Infrastruktur Kota Tahun 2022 - Harvi Dasnoer; Dwi Rizka Witria Gewe; Hilda Mayang Sari; Aldri Frinaldi; Syamsir Syamsir (Peneliti.net, 2023)
Padang City as the capital city of West Sumatra Province with its economic center is very committed to Regional Development. This can be seen from the many building and infrastructure development activities that are growing rapidly from year to year. The management of buildings is one of the physical forms of space utilization in the city of Padang. Buildings that are erected need to be arranged so that they are in accordance with the function and purpose of using the building. Building Construction Permit (IMB) or currently called Building Approval (PBG) is one of the building administration instruments that will become a regulatory and controlling instrument, for the construction and maintenance of buildings in the city of Padang.This article discusses the formulation of a public policy, namely the Mayor of Padang Regulation Number 378 of 2022 concerning the City Building and Infrastructure Supervision Team in 2022. This research aims to identify and analyze the reasons behind the Padang City Government sparking the idea to form a Building and Infrastructure Monitoring Team Cities in 2022. Through the approach used in this study, namely a qualitative approach, researchers can find out and carry out an analysis of the formulation process for various reasons until the issuance of a policy product. The results of this study are the formulation process which is carried out through four stages with a typical formulation model, namely a mixed model between the institutional model and the rationalism model.